Rendimiento de dos variedades de coliflor (Brassica oleracea L.), sometido a tres abonos orgánicos bajo sistemas protegidos de micro túneles en el cantón Cayambe, provincia de Pichincha - Salazar Rosero, Ana Marisol (2015)
This research was conducted in the field of Romerillos, parish Ayora, Canton Cayambe, Pichincha province; located at Km 10 via Cayambe - Olmedo, between the geographical coordinates: 00° 05' 30,34 "N, 78° 05' 13.08" W at an altitude of 3.138 meters. As seed material varieties Nevada and Kangoo, whose treatments were composed by the varieties of cauliflower and sources of organic fertilizers were used. The present investigation "Random complete block" experimental design was used with factorial arrangement A x B, in 4 replications. To determine the significant difference of the treatments Duncan test at 5% probability was applied. The objectives were to evaluate different organic fertilizer to crop yield response of two varieties of cauliflower; determine the variety most adaptable system of micro tunnels and economically analyze the treatments studied. During the growing season the work of soil analysis, soil preparation, land leveling, soil disinfection, fertilizer, construction of micro tunnels beds, transplant, watering, weeding, hoeing, plant protection and harvesting took place......